2002
DOI: 10.1074/jbc.m202869200
|View full text |Cite
|
Sign up to set email alerts
|

A 29-kDa Protein Associated with p67 Expresses Both Peroxiredoxin and Phospholipase A2 Activity and Enhances Superoxide Anion Production by a Cell-free System of NADPH Oxidase Activity

Abstract: Production of toxic oxygen metabolites provides a mechanism for microbicidal activity of the neutrophil. The NADPH oxidase enzyme system initiates the production of oxygen metabolites by reducing oxygen to form superoxide anion (O 2 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
34
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 37 publications
(53 reference statements)
3
34
0
Order By: Relevance
“…A similar Prdx6 requirement was demonstrated for agonist-mediated ROS production by alveolar macrophages. A similar conclusion regarding a role for Prdx6 in NOX2 activation was reached in a previous in vitro study of PMN in which ROS production was approximately doubled by the presence of recombinant Prdx6 (also known as p29); this latter study used a reconstituted system consisting of isolated plasma membrane from PMN and recombinant cytosolic proteins (7). Although the recombinant Prdx6 (p29) exhibited both PLA 2 FIGURE 8.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A similar Prdx6 requirement was demonstrated for agonist-mediated ROS production by alveolar macrophages. A similar conclusion regarding a role for Prdx6 in NOX2 activation was reached in a previous in vitro study of PMN in which ROS production was approximately doubled by the presence of recombinant Prdx6 (also known as p29); this latter study used a reconstituted system consisting of isolated plasma membrane from PMN and recombinant cytosolic proteins (7). Although the recombinant Prdx6 (p29) exhibited both PLA 2 FIGURE 8.…”
Section: Discussionmentioning
confidence: 70%
“…The PLA 2 activity catalyzes the hydrolysis of the acyl group at the sn-2 position of glycerophospholipids, with special affinity for phosphatidylcholine, to produce free fatty acids and a lysophospholipid; the peroxidase activity uses glutathione as the co-factor for reduction of hydroperoxides, including phospholipid hydroperoxides (6). In a previous study, Prdx6 (therein called p29) was found to participate in the activation of NOX2 in human neutrophils (7). However, the mechanism by which Prdx6 might activate NOX2-mediated ROS generation was not determined.…”
mentioning
confidence: 99%
“…The enzymatic kinetics observed for the removal of H 2 O 2 is comparable to that of peroxiredoxins from P. falciparum, C. elegans, human neutrophils, and Pisum sativum, where similar peroxidase assays were used (Fig. 1D) (8,26,27,32).…”
Section: Resultsmentioning
confidence: 85%
“…As described above, this lysosomal-type activity in the lung is inhibited by MJ33 (3, 17). PLA 2 activity that is Ca 2ϩ -independent, maximal at pH 4, and inhibited by MJ33 has been demonstrated for Prdx6 isolated from lungs (25,29) and polymorphonuclear leukocytes (46) and for recombinant Prdx6 (12,25). Prdx6 mRNA and protein are widely distributed throughout mammalian tissues, but content in the lung is greater than in other major organs (25,47).…”
Section: Fig 4 Degradation Of [ 3 Hmentioning
confidence: 99%